An Affine Scaling Algorithm for Biobjective Linear Programming - Menezes, Marco Antonio Figueiredo; Maculan, Nelson (Journal of the Operations Research Society of China (Internet), 2024)
Given a biobjective linear programming problem, we develop an affine scaling algorithm with min-max direction and demonstrate its convergence for an efficient solution. We implement the algorithm for some minor issues in the literature.